Status of Maternity Services in Karnali Academy of Health Sciences - Bhattari, Saraswoti Kumari Gautam; Dahal, M.; Budha, M.R. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Access to proper medical attention and hygienic conditions during delivery can reduce the risk of complications and infections for the mother and baby. Health facility-based delivery is considered a critical strategy to improve maternal health. This study aimed to identify the status of maternity service in Karnali Academy of Health Science (KAHS), Jumla. Methods: A hospital based retrospective study was done in maternity ward of KAHS teaching hospital, Jumla. Total 855 women admitted in maternity ward with obstetrical problem and labour pain were included in the study from July 16, 2017 to July 16, 2018. Sampling technique was census and cases were selected from record section. Data was analyzed by using descriptive statistics. Results: There were total 855 obstetrical cases with labour pain and other obstetrical conditions. Among them 673 (78.71%) cases were in labour pain, 543 (80.68%) had spontaneous vaginal delivery, 104 (15.45%) had cesarean section. Among the 678 neonates; 650 (95. 87%) were live born baby, 28 (4.12%) were still birth, 13 (1.91%) died in neonatal period. Furthermore, among 855 obstetric cases 109 (12.74%) had obstetrical complications, and 116 (13.56%) received specific obstetrical management for complications. Conclusions: Though there was no any maternal death in the KAHS nearly 2% neonatal death was found. Therefore, special management facility should be improved for the survival of neonates in future.